ANALISIS PENGARUH RISIKO TERHADAP RETURN YANG DIHARAPKAN UNTUK MENENTUKAN PILIHAN BERINVESTASI PADA SAHAM JAKARTA ISLAMIC INDEX (JII) - Safitri, Ervita (MOTIVASI, 2017)
Purpose - The objective of this study was to assess the risk of the stock return by using CAPM model to determine the investment option at Jakarta Islamic Index in the Indonesia Stock Exchange (BEI) and to find the risk of the return which was expected by CAPM Model.Design/methodology - The population of this study was 52 companies which were listed at JII in 2010-2014. The sample of this study was chosen by using purposive sampling method. The numbers of the companies were 12 companies. Data analysis technique in this study was by using the monthly closing share price dara registered in JII, JII market index, and interest rates of SBI.Findings – The result of this study showed that out of twelve companies, there were four stocks that could be used as the investment option, namely PT. Alam Sutra Reality, tbk, PT. Astra International, tbk, PT. Lippo Karawaci, tbk, PT. Telekomunikasi Indonesia, tbk. The result of hypothesis testing with a simple linear regression t-test found that t value > t table (-24,249>-2,228) with significant value (0,00<0,05) , it indicated that there was a significant influence between beta and CAPM expected return.